BUDAYA ORGANISASIONAL DAN KNOWLEDGE SHARING TERHADAP KINERJA PEGAWAI - Rathi Nuryani Achmad; Adnan Rajak (Jurnal Manajemen Sinergi, 2020)
Objective: The purpose of this study are: (1) Analyzing the influenceof Organizational Culture on the performance of civil servants at theOffice of Public Work of Ternate City; (2) To analyze the influence ofKnowledge Sharing on the performance of of civil servants at theOffice of Public Work of Ternate City; and (3) Analyzing the influenceof work organizational culture and Knowledge Sharing simultaneouslyon the performance of of civil servants at the Office of Public Work ofTernate City. The number of sample is 51 employees.Methodology: The test equipment used is multiple regressionanalysis using statistical package for social scientists (SPSS) as astatistical test tool.Finding: H1, H2, and H3 are accepted at the 5% confidence level.Conclusion: The result of the research shows that: (1) OrganizationalCulture has a positive and significant influence partially on theperformance of civil servants at the Office of Public Work of TernateCity; (2) Knowledge Sharing has a positive and significant influencepartially on the performance of civil servants at the Office of PublicWork of Ternate City. and (3) Organizational Culture (X1) andKnowledge Sharing (X2) simultaneously have a positive andsignificant effect on civil servants at the Office of Public Work ofTernate City. This result is based on a F value greater than F table ora smaller significance value (0,000) of alpha value (0.05).